Increasing intensity directly increases the perceived warmth of primary colors - Billy R. Hammond; Colin R. Gardner; Billy R. Wooten; Lisa Renzi-Hammond (Scientific Reports)
Abstract There is a long history of linking the perceptions of temperature and color (the “Hue-heat hypothesis”): red (R) and yellow (Y) are often considered warm, whereas blue (B) and green (G) are cool. Past studies, however, have largely used relatively broad-band light at a fixed intensity to test these relations. We tested whether increasing the intensity of highly saturated primary colors would lead to a concomitant change in the perceived temperature of those colors. 20 young healthy participants (M = 24.80±3.53 years; 45% female; 5% Hispanic; 45% non-White) with normal color vision were tested. An optical system with a Xenon-arc light source, chromatic filters (peak l = 465, 530, 572, 652 nm), and a circular neutral density wedge to vary intensity were used (5 intensity levels). Temperature perception was assessed using an ordinal scale from – 5 (coolest) to + 5 (warmest). The order of the colors used and the intensity levels were varied randomly. Considering the average across intensity levels, B (-1.87) and G (+ 1.09) were considered the coolest, whereas Y (+ 2.1) and R (+ 3.75) were considered the warmest colors. All colors, however, warmed with increasing intensity. A linear regression fit to the averaged data across luminance explained the majority of the variance: B (r2 = 0.78), Y (r2 = 0.93), G (r2 = 0.98), and R (r2 = 0.92). Consistent with past data, our results show that color is significantly linked with temperature perception. Increasing the luminance of colors, however, strongly shifts the perception toward increased warmth.